2021
DOI: 10.3389/fmicb.2021.651279
|View full text |Cite
|
Sign up to set email alerts
|

Endomembrane-Targeting Plasmodiophora brassicae Effectors Modulate PAMP Triggered Immune Responses in Plants

Abstract: Plasmodiophora brassicae is a devastating obligate, intracellular, biotrophic pathogen that causes clubroot disease in crucifer plants. Disease progression is regulated by effector proteins secreted by P. brassicae. Twelve P. brassicae putative effectors (PbPEs), expressed at various stages of disease development [0, 2, 5, 7, 14, 21, and 28 days post inoculation (DPI)] in Arabidopsis and localizing to the plant endomembrane system, were studied for their roles in pathogenesis. Of the 12 PbPEs, seven showed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…The 2OG-Fe (II) oxygenase (SPQ94350.1 – Supplementary Table 6 ), presented low covariance at 21 dai but was also expressed at 14 dai. This exact same gene [corresponding to PBRA003835 in the first genome draft of P. brassicae ( Schwelm et al, 2015 )] has been recently identified as significant inhibitor of programmed cell death (PCD) in the clubroot interaction, and designated as PbPE15 ( Hossain et al, 2021 ). Another group of genes was annotated to processes of nutrient acquisition and transformation, including carbohydrates and nitrogen derivates metabolism (glucosidase II beta subunit, aldolase 1-epimerase, allantoicase, and amidohydrolase), which is in agreement with overall patterns of secretomes in biotrophic fungi ( Kim et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2OG-Fe (II) oxygenase (SPQ94350.1 – Supplementary Table 6 ), presented low covariance at 21 dai but was also expressed at 14 dai. This exact same gene [corresponding to PBRA003835 in the first genome draft of P. brassicae ( Schwelm et al, 2015 )] has been recently identified as significant inhibitor of programmed cell death (PCD) in the clubroot interaction, and designated as PbPE15 ( Hossain et al, 2021 ). Another group of genes was annotated to processes of nutrient acquisition and transformation, including carbohydrates and nitrogen derivates metabolism (glucosidase II beta subunit, aldolase 1-epimerase, allantoicase, and amidohydrolase), which is in agreement with overall patterns of secretomes in biotrophic fungi ( Kim et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The 2OG-Fe (II) oxygenase (SPQ94350.1 -Supplementary Table 6), presented low covariance at 21 dai but was also expressed at 14 dai. This exact same gene [corresponding to PBRA003835 in the first genome draft of P. brassicae (Schwelm et al, 2015)] has been recently identified as significant inhibitor of programmed cell death (PCD) in the clubroot interaction, and designated as PbPE15 (Hossain et al, 2021). Another group Alpha helices are highlighted in purple and beta sheets are in green.…”
Section: Plasmodiophora Brassicae Secretome Transcripts When Infecting 'Brutor' At 21 Daimentioning
confidence: 99%
“…While PbBSMT targets the SA pathway, other (putative) P. brassicae effectors have been identified by bioinformatic methods only [72] and possible functions only for a few suggested [73][74][75][76]. Among these were a kinase [73], a putative E3 ubiquitin ligase [74], an apoplastic protein able to directly interact with and inhibit cruciferous papain-like cysteine proteases [75], as well as endomembrane-localized effectors that modulate PAMP triggered immunity [76]. Other proteins, for which a function has been implicated, do not seem to fall under the category "effector", e.g., the protease PRO1 that possibly helps in spore germination [77].…”
Section: Discussionmentioning
confidence: 99%
“…In tobacco, a collection of putative effectors has been analyzed for their localization and possible function [ 85 ]. Several were able to elicit PAMP-triggered immunity in this system, and some were found in the endomembrane system, which indicated their possible translocation into the host plant.…”
Section: Plasmodiophora Brassicae Genomes Across the Globementioning
confidence: 99%
“…To summarize the numerous questions remaining: Where are the effectors localized in planta? Some data stem from heterologous transient expression in tobacco [ 38 , 85 , 86 ], which is not a transformation system close to a host of P. brassicae . Others have employed the host plant A. thaliana [ 73 , 74 ] to address the question of whether they are functional not only in vitro but also in planta.…”
Section: Plasmodiophora Brassicae Genomes Across the Globementioning
confidence: 99%